2015
DOI: 10.1038/srep10152
|View full text |Cite
|
Sign up to set email alerts
|

The transgenic cloned pig population with integrated and controllable GH expression that has higher feed efficiency and meat production

Abstract: Sustained expression of the GH gene has been shown to have detrimental effects on the health of animals. In the current study, transgenic founder pigs, with controllable pig growth hormone (pGH) expression, were cloned via the handmade cloning method (HMC), and pGH expression levels were examined at the cellular and organismal levels. The serum pGH levels in 3 founder male pigs were found to be significantly higher after induction with intramuscular injection of doxycycline (DOX) compared to baseline. A daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Pig models are often favored over rodent models due to their clinical relevance and high similarity to human physiology and anatomy 1 2 3 . Traditionally, transgenic pigs have been produced by integrating a gene sequence or a transgene into the genome in a random manner, in which the transgene can be inserted anywhere in the genome 4 . Random integration of a transgene often leads to unstable phenotypes, gene silencing and unpredictable gene expression, and in some cases, this process is mutagenic.…”
mentioning
confidence: 99%
“…Pig models are often favored over rodent models due to their clinical relevance and high similarity to human physiology and anatomy 1 2 3 . Traditionally, transgenic pigs have been produced by integrating a gene sequence or a transgene into the genome in a random manner, in which the transgene can be inserted anywhere in the genome 4 . Random integration of a transgene often leads to unstable phenotypes, gene silencing and unpredictable gene expression, and in some cases, this process is mutagenic.…”
mentioning
confidence: 99%
“…The special interest assigned to GH is probably due to husbandry in which several land-living and aquatic animals have been genetically modified to excrete more GH and thus could grow faster to slaughtering size, e.g. coho salmon (Oncorhynchus kisutch) (Raven et al, 2008) and pig (Ju et al, 2015). Several studies have been conducted with both transgenic and hormone-implanted trout and coho salmon.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of food intake and the ratio of food intake to metabolic body mass as indicated by RFBW were reduced in both FSC-S/normal and FSC-S/HCL mice, their FEI values markedly increased as compared with the corresponding un-supplemented animals. This indicated that some ingested food/energy is not converted into body mass in both normal and HCL mice supplemented with FSC-S. FEI (weight gain per unit of food ingested) is an index reflecting the amount of feed to produce one kilogram of meat in animal husbandry industry [ 32 36 ]. In this study, FEI reflects the FSC-S-induced body weight loss in normal and HCL mice.…”
Section: Discussionmentioning
confidence: 99%